2016
DOI: 10.1136/bjophthalmol-2016-309319
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subfoveal choroidal thickness and reduction of serum levels of vascular endothelial growth factor in patients with POEMS syndrome

Abstract: The significant correlation between the CT and the serum level of VEGF may offer clues on the pathogenesis of ocular diseases of POEMS syndrome and on the role of serum VEGF on the choroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…However, vascular endothelial growth factor (VEGF) is considered to be a pivotal factor in the progressing of many clinical features [1], including papilledema. The connection between papilledema and serum VEGF has already been reported, both in our previous study and in studies of other ophthalmologists or hematologists, based on peripapillary retinal thickness (pRT) and subfoveal choroidal thickness [3][4][5][6]. But the measurements of these two parameters were inconvenient and costly, thus impractical for routine ODE assessment.…”
Section: Introductionmentioning
confidence: 82%
“…However, vascular endothelial growth factor (VEGF) is considered to be a pivotal factor in the progressing of many clinical features [1], including papilledema. The connection between papilledema and serum VEGF has already been reported, both in our previous study and in studies of other ophthalmologists or hematologists, based on peripapillary retinal thickness (pRT) and subfoveal choroidal thickness [3][4][5][6]. But the measurements of these two parameters were inconvenient and costly, thus impractical for routine ODE assessment.…”
Section: Introductionmentioning
confidence: 82%
“…Although patients with the POEMS syndrome have been shown to have an overload of systemic extravascular fluid, e.g., peripheral oedema, pleural effusions, ascites, and pericardial effusions, the ODE and increased choroidal thickness 8,16,17 were the only structural abnormalities in the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…18 We have reported that the serum level of VEGF was correlated with the subfoveal choroidal thickness. 16,17 In the choroidal vessels, serum with a high concentration of VEGF could leak into the choroidal interstitial fluid through the fenestrated choriocapillaris, and the VEGF could increase the permeability by affecting VEGFR2. It was reported from the findings in animal experiments that the blood stream reaches the axons of the optic nerve through the border tissue of Elschnig from the adjacent choroidal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal vascular hyperpermeability [35, 36] and increased serum level [51] are also considered to be associated with choroidal thickening.…”
Section: Physiology Of Choroidmentioning
confidence: 99%